2018
DOI: 10.1590/1413-81232018239.15922016
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à cobertura do Sisvan Web para crianças menores de 5 anos, nos municípios da Superintendência Regional de Saúde de Belo Horizonte, Brasil

Abstract: Resumo O presente trabalho teve como objetivo analisar fatores associados à cobertura do Sistema de Vigilância Alimentar e Nutricional (Sisvan Web) para crianças menores de cinco anos, nos municípios da Superintendência Regional de Saúde de Belo Horizonte (SRS-BH). Foram coletados dados da cobertura do Sisvan Web nos meses de setembro e outubro de 2012, período em que foi enviado um “Questionário semiestruturado sobre o funcionamento do Sisvan” às referências técnicas dos municípios avaliados. A cobertura foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
(12 reference statements)
0
7
1
3
Order By: Relevance
“…The coverage of 63.3% for children under 5 years of age found in the present study is higher than that estimated for this population group in Brazil in 2012 (27.9%) 6 and for specific locations in the country, such as Rio Grande do Sul in 2010 (10.5%), 13 municipalities of the Regional Health Superintendency of Belo Horizonte from September to October 2012 (5.6%), 15 and 2 cities in Paraíba in 2010 (6.5 and 10.1%). 5 Therefore, the data obtained from SISVAN Web in the municipalities of this study seem to have good representativeness, based on the reported coverage.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The coverage of 63.3% for children under 5 years of age found in the present study is higher than that estimated for this population group in Brazil in 2012 (27.9%) 6 and for specific locations in the country, such as Rio Grande do Sul in 2010 (10.5%), 13 municipalities of the Regional Health Superintendency of Belo Horizonte from September to October 2012 (5.6%), 15 and 2 cities in Paraíba in 2010 (6.5 and 10.1%). 5 Therefore, the data obtained from SISVAN Web in the municipalities of this study seem to have good representativeness, based on the reported coverage.…”
Section: Discussioncontrasting
confidence: 78%
“…20 Thus, training professionals in anthropometry is essential to ensure the quality necessary for anthropometric measurements and SISVAN Web information, as previously suggested. 3,15,20,21 Training should take place once every six months and whenever a change is made in the team of professionals working in the system. 21 Besides the statistical significance, the differences found between prevalence rates suggest the possibility of misdiagnoses of anthropometric abnormalities among children in health services.…”
Section: Discussionmentioning
confidence: 99%
“…The indicators used in this analysis were: (i) national coverage of nutritional status of children in all federal states from 2008 to 2018 -percentage of children accompanied in the Sisvan, calculated as the number of children (5)(6)(7)(8)(9) registered in the system divided by the population of children that use the public health service in the same age group in those years, multiplied by 100; and (ii) completeness of data -obtained by dividing the number of municipalities that had registries in the system per year, by the total number of municipalities that could have registered per year, multiplied by 100.…”
Section: Methodsmentioning
confidence: 99%
“…Studies done in the last years have pointed to challenges and limitations of the Sisvan however, including: low coverage, insu cient training for data collection and log system, lack of knowledge of the professionals regarding data interpretation and the direct relationship of the data collection process with the cash transfer program Bolsa Familia (Family Allowance), since a majority of the Sisvan coverage is due to measurements done for this initiative [8,9]. Literature also indicates there is still a lot to be improved in terms of data collection and management [10][11][12], becoming evident that national surveillance strategies are still not used in their full capacity at municipal levels [13,14], indicating a gap between the data generated by the system and its nal usage [11].…”
Section: Introductionmentioning
confidence: 99%
“…21 Another study conducted by the same group/health region in 2012 in the same catchment area but with children under 5 years old found average coverage of 5.59%. 22 Progress with Food and Nutrition Surveillance contributes to the effective organization of nutrition care by the SUS, as provided for in the National Food and Nutrition Policy (PNAN): by means of nutritional diagnosis of the population, individuals and groups at nutritional risk are identified, thus contributing to updating and planning public food and nutrition policies. 11 As such, the increase in coverage identified in the Northern Region over the years analyzed reflects the The Ministry of Health, via its General Food and Nutrition Coordination Body, has supported state and municipal governments in overcoming the great challenge of Food and Nutrition Surveillance, by promoting training courses and workshops, preparing and disseminating instructional materials, among other initiatives.…”
Section: Methodsmentioning
confidence: 99%